Peranan PCO dalam Bidding Konferensi Asosiasi: 2021 Asia Pacific Cities Summit - Miranda Putri; Christina L. Rudatin (Bisnis Event, 2020)
The party that is supposed to bid is the local association party. However, the bidding initiative can come from the PCO. PT Rajawali Pacific Internusa is a PCO that has the initiative to do "Asia Pacific Cities Summit & Mayor’s Forum" bidding in Brisbane, Australia in July 2019 along with INACEB, the Indonesian Ministry of Tourism and related associations. Rajawali Convex's role in this bidding was as the party who initiated the 2021 APCS bidding as well as being the leader and director when the bidding team arrived, when they were going to attend the bidding and also took care of the accommodation during the event in Brisbane. In addition, the PCO also acted as the interviewees when the jury asked questions. The research method used by the writer is a qualitative. The data collection method used are the observation method, the interviewing method and documentation. The data complile method used by the writer is a qualitative descriptive analysis method that analyzes the data by describing, explaining, interpreting the data obtained during work practices while comparing it with related theories. This journal will give readers an overview of the role of the PCO before and during the bidding event for the "2021 Asia Pacific Cities Summit & Major’s Forum" Association's Conference. The result of the study found that PCO can play a role as the party that initiates bidding for Association’s Conference. PCO is a party that prepares the requirements for the bidding and also during the bidding.